Strategi Dan Praktik Terbaik Untuk Melindungi Data Di Universitas Bhayangkara Jakarta Raya - Arya Radithya; Iqbal Mahdi Bisyafaa; Gilang Gs Putra (Journal of Informatic and Information Security, 2024)
Cybersecurity is a crucial aspect in protecting important data at universities, including Universitas Bhayangkara Jakarta Raya, which handles student, staff, and financial data. This article discusses strategies as well as best techniques that can be employed to strengthen the university's data security. The research covers risk assessment, security training, secure authentication, data backup, system maintenance, network security, security policies, threat monitoring, encryption, and external collaboration. By adopting these strategies, Universitas Bhayangkara Jakarta Raya can minimize risks and enhance the security of their digital information. The research findings indicate that implementing a layered security system can improve the effectiveness of data protection at the university.